2012
DOI: 10.1116/1.3678208
|View full text |Cite
|
Sign up to set email alerts
|

Molecular beam epitaxy growth of AlGaN quantum wells on 6H-SiC substrates with high internal quantum efficiency

Abstract: The authors report the development of high internal quantum efficiency AlN/AlGaN/AlN double heterostructures and AlGaN/AlN multiple quantum wells (MQWs) grown on 6H-SiC and 4H-SiC substrates of various miscuts by plasma-assisted molecular-beam epitaxy. The authors find that the luminescence spectra for identical MQWs show a single peak across the gap, with a wavelength that is redshifted by $20 nm as the excess Ga during growth of the wells increases. The internal quantum efficiency of the double heterostructu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 26 publications
0
21
0
Order By: Relevance
“…[108] Zhang et al reported that such AlGaN/ AlN MQWs emitting at 245 nm have an IQE of 68%. [107] These values of IQE for AlGaN MQWs emitting at 250 nm are comparable with those of InGaN MQWs. [106] In the case of InGaN QWs, the high IQE is generally attributed to band-structure potential fluctuations due to compositional inhomogeneities in these alloys.…”
Section: Development Of Algan Qws With High Iqementioning
confidence: 70%
See 1 more Smart Citation
“…[108] Zhang et al reported that such AlGaN/ AlN MQWs emitting at 245 nm have an IQE of 68%. [107] These values of IQE for AlGaN MQWs emitting at 250 nm are comparable with those of InGaN MQWs. [106] In the case of InGaN QWs, the high IQE is generally attributed to band-structure potential fluctuations due to compositional inhomogeneities in these alloys.…”
Section: Development Of Algan Qws With High Iqementioning
confidence: 70%
“…[107] Growth of AlGaN alloys and QWs on SiC for emitters has several advantages. The lattice mismatch between SiC and AlN is only ∼1%.…”
Section: Development Of Algan Qws With High Iqementioning
confidence: 99%
“…In the recent years, AlGaN-based UV lightemitting diodes (LEDs) [1,2] have appeared as promising candidates to replace mercury lamps due to their advantages of compactness, portability, long lifetime and environmental friendliness. Although AlGaN/AlN quantum wells (QWs) with high internal quantum efficiency (IQE) have been reported [3][4][5], the fabrication of electrically-driven UV LEDs must face the challenges of p-type doping and contacting high-Al-content AlGaN layers, which result in extremely low external quantum efficiency [6] (EQE < 1% for UV LEDs emitting below 250 nm). Electron-pumped UV (EPUV) sources incorporating a miniaturized electron source [7] have been introduced as an alternative approach to circumvent the p-doping issue.…”
Section: Introductionmentioning
confidence: 99%
“…The symmetric (0002) and asymmetric (101 2) full width have fitted widths of 394 and 778 arc sec which is less than that of the Cr-doped GaN. The dislocation density in this film was determined by measuring the x-ray rocking curves of (0002) and (101 2) diffraction spots and fitting the data to the formula [26][27][28]:…”
Section: Resultsmentioning
confidence: 99%